Evidence for the need to update the Chilean standard for school furniture dimension specifications - Castellucci, H. I. (2016)
Some countries decide to use standards to define the type of furniture dimensions that should be used according to students' anthropometric characteristics. The aim of this paper is to generate data to update the standard for Chilean school furniture using student anthropometric data. The sample used involved 3078 students. Data collection included eight anthropometric dimensions. A strict procedure was followed to define six furniture school dimensions. The definition of the compatibility between students' characteristics and furniture dimensions was done using the concept of mismatch computed through a set of equations. The results showed differences in mismatch levels between the two compared approaches, with lower mismatch found using the new proposed approach – the updated standard (UpS). Seat depth presents the greatest difference in mismatch, with values of 43% for the current Chilean standard (ChS) and 17% for the UpS. Also, seat height match values are almost the same (100%); however, it is important to mention that the level of match could drop to 82% in the ChS if the furniture selection was already carried out, as suggested in the standard itself, by using the Stature. Finally the UpS presents a higher covered range in the six furniture dimensions. The obtained results reflect the need to update the data and the procedure for school furniture selection presented by the current Chilean standard. Relevance for industry: this paper presents relevant data to be used by both school furniture designers, as well as by those responsible for the furniture selection at schools. In addition, proof is presented that school furniture standards need to be updated periodically in order to better fit the students’ anthropometric characteristics.